Effects of Different Oocyte Activation Procedures on Development and Gene Expression of Porcine Pre-Implantation Embryos - Cervera, R. P.; Silvestre, Miguel A.; Marti, N.; García-Mengual, Elena; Moreno, R.; Stojkovic, M. (2017)
Among the factors that affect the efficiency of somatic cell nuclear transfer (SCNT) in pigs, the activation protocol is the most variable among the current SCNT procedures. The aim of this study is focused on defining an efficient activation treatment of porcine oocytes. In Experiment 1, we studied the effects of nine different oocyte activation procedures (including chemical-and electrical-based treatments) on parthenogenetic embryo development. In Experiment 2, we studied the effect of the more efficient activation procedures on the gene expression profile of Oct4 and Igf2r in parthenogenetic blastocysts. In conclusion, ionomycin as a first calcium stimulus is not able to activate porcine oocytes efficiently in comparison with electric procedures. Electrical treatments with 6-DMAP significantly increased the level of Oct4 expression, whereas the single and double pulse treatments alone maintained the same profile as the IVF group.